2022
DOI: 10.1007/s00445-022-01560-w
|View full text |Cite
|
Sign up to set email alerts
|

Linking ground-based data and satellite monitoring to understand the last two decades of eruptive activity at Sangay volcano, Ecuador

Abstract: Sangay is one of the most active volcanoes in Ecuador, as it has been almost continuously erupting at least since the 17th century. However, because of its remote location and low associated risk to human population, little is known about its eruptions. Here we summarize Sangay's volcanic activity from January 2001 to May 2020, based on ground-based data, satellite-derived observations, and chemical analysis of its erupted products. During the analyzed period, Sangay's activity changed from continuous to episo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…No correlation or pattern is observed with the distance from the vent. We note that the composition of the September 20, 2020 ash samples fall within the compositional field of the Sangay III edifice (Monzier et al, 1999) but is more mafic than the composition analyzed from the recent decades (Monzier et al, 1999;Vasconez et al, 2022) (Figure 9). We chose the samples SAN-20-25 and SAGA-20A to perform an exploratory componentry analysis (Supplementary Material S5).…”
Section: Geochemistry and Componentrymentioning
confidence: 76%
See 4 more Smart Citations
“…No correlation or pattern is observed with the distance from the vent. We note that the composition of the September 20, 2020 ash samples fall within the compositional field of the Sangay III edifice (Monzier et al, 1999) but is more mafic than the composition analyzed from the recent decades (Monzier et al, 1999;Vasconez et al, 2022) (Figure 9). We chose the samples SAN-20-25 and SAGA-20A to perform an exploratory componentry analysis (Supplementary Material S5).…”
Section: Geochemistry and Componentrymentioning
confidence: 76%
“…Unfortunately, due to frequent power and transmission outages likely due to repeated ash fallout, SAGA did not record the September 20, 2020 eruptive pulse. The study by Vasconez et al (2022) found that a broadband seismic sensor with low anthropogenic noise levels located 67 km to the north-northeast (PUYO, Figure 1B) generally had fewer outages than SAGA and was a suitable alternative for identifying high-magnitude explosive activity from Sangay. Frequency-filtered RSAM (Real-time Seismic Amplitude Measurement) is computed in 1-min windows at the IG-EPN for PUYO seismic records in the 0.6-1.2 Hz band (raw seismic records and filtered RSAM data for September 20, 2020 are available in Supplementary Material S1).…”
Section: Methodology Seismic Monitoringmentioning
confidence: 99%
See 3 more Smart Citations